Think Less, Invest More: The Emotional and Social Influences Behind Millennial Decisions - Rifqi Amrulloh; Jakiroh (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
This study aims to analyze the influence of emotional intelligence and social influence on investment decisions in digital investment applications for millennials in South Kalimantan, mediated by risk perception. The study used a quantitative approach with explanatory research, collecting data through a survey with a Likert-scale questionnaire to 280 millennial investors in South Kalimantan. Data were analyzed using Structural Equation Modeling (SEM-PLS) 4 to test the relationship between variables.